2007
DOI: 10.1165/rcmb.2006-0238oc
|View full text |Cite
|
Sign up to set email alerts
|

Integrin αvβ5 Regulates Lung Vascular Permeability and Pulmonary Endothelial Barrier Function

Abstract: Increased lung vascular permeability is an important contributor to respiratory failure in acute lung injury (ALI). We found that a function-blocking antibody against the integrin ␣v␤5 prevented development of lung vascular permeability in two different models of ALI: ischemia-reperfusion in rats (mediated by vascular endothelial growth factor [VEGF]) and ventilation-induced lung injury (VILI) in mice (mediated, at least in part, by transforming growth factor-␤ [TGF-␤]). Knockout mice homozygous for a null mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
145
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(160 citation statements)
references
References 89 publications
13
145
1
Order By: Relevance
“…In a lung model of I/R, characterized by downregulation of TM along with activation of coagulation and inflammation (30)(31)(32)(33)35), scFv/TM was superior to sTM in reducing fibrin deposition and cytokine production and provided greater protection of lung function. scFv/TM also inhibited elevation of Egr-1, a pivotal participant in I/R-mediated lung injury (31,33,45).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a lung model of I/R, characterized by downregulation of TM along with activation of coagulation and inflammation (30)(31)(32)(33)35), scFv/TM was superior to sTM in reducing fibrin deposition and cytokine production and provided greater protection of lung function. scFv/TM also inhibited elevation of Egr-1, a pivotal participant in I/R-mediated lung injury (31,33,45).…”
Section: Discussionmentioning
confidence: 97%
“…I/R causes thrombosis and inflammation (32)(33)(34)(35)(36)(37)(38). We detected reduced expression of TM and a concomitant increase in the deposition of fibrin in lungs after I/R ( Figure 3A).…”
Section: Anticoagulant and Antiinflammatory Effects Of Scfv/tm In Lunmentioning
confidence: 97%
“…For example, in bleomycin-induced pulmonary edema, TGFb promotes vascular leakage by acting directly on pulmonary endothelial cells in concert with integrin a5b1 (Pittet et al, 2001;Su et al, 2007). TGFb also induces the expression of angiopoietin-like protein 4 (Angpt-4) that, in turn, disrupts endothelial cell junctions, increases leakage, and promotes tumor cell emigration and metastasis to the lungs (Padua et al, 2008).…”
Section: Tgfb Regulates Vascular Homeostasis and The Response To Tissmentioning
confidence: 99%
“…Sheppard et al [74,75] have demonstrated that β3 is protective (i.e.,β5-null mice are sensitive) to endotracheal and intraperitoneal LPS and cecal ligation and puncture (CLP), whereas Pittet et al have shown that β5 enhances (i.e.,β5-null mice are resistant) to lung vascular leak after infection, [76] ischemia/reperfusion, or VILI [77]. Meanwhile, a new publication by Ding [78] suggested that the integrin family member β-6 is known to play an important role in regulating lung inflammation, macrophage protease expression, and pulmonary edema during the process of ALI.…”
Section: Wisp1 and Toll-like Receptor (Tlrs) Integrin-mediated Signamentioning
confidence: 99%